Shocked Quartz in Polymict Impact Breccia from the Upper Cretaceous Yallalie Impact Structure in Western Australia - Cox, M.; Cavosie, Aaron; Ludovic, F.; Timms, N.; Bland, P.; Miljkovic, Katarina; Erickson, T.; Hess, B. (John Wiley & Sons, Inc., 2019)
Yallalie is a ~12 km diameter circular structure located ~200 km north of Perth, Australia. Previous studies have proposed that the buried structure is a complex impact crater based on geophysical data. Allochthonous breccia exposed near the structure has previously been interpreted as proximal impact ejecta; however, no diagnostic indicators of shock metamorphism have been found. Here we report multiple (27) shocked quartz grains containing planar fractures (PFs) and planar deformation features (PDFs) in the breccia. The PFs occur in up to five sets per grain, while the PDFs occur in up to four sets per grain. Universal stage measurements of all 27 shocked quartz grains confirms that the planar microstructures occur in known crystallographic orientations in quartz corresponding to shock compression from 5 to 20 GPa. Proximity to the buried structure (~4 km) and occurrence of shocked quartz indicates that the breccia represents either primary or reworked ejecta. Ejecta distribution simulated using iSALE hydrocode predicts the same distribution of shock levels at the site as those found in the breccia, which supports a primary ejecta interpretation, although local reworking cannot be excluded. The Yallalie impact event is stratigraphically constrained to have occurred in the interval from 89.8 to 83.6 Ma based on the occurrence of Coniacian clasts in the breccia and undisturbed overlying Santonian to Campanian sedimentary rocks. Yallalie is thus the first confirmed Upper Cretaceous impact structure in Australia.